To spark a match [large type] - Turano, Jen (Turano, Jen. Matchmakers (Series), 2024)
"After five unsuccessful Seasons on the marriage mart, Miss Adelaide Duveen has resigned herself to the notion that she's destined to remain a spinster forever--a rather dismal prospect, but one that will allow her to concentrate on her darling cats and books. However, when she inadvertently stumbles upon Mr. Gideon Abbott engaged in a clandestine activity during a dinner party, Adelaide finds herself thrust into a world of intrigue that resembles the plots in the spy novels she devours. Former intelligence agent Gideon Abbott feels responsible for Adelaide after society threatens to banish her because of the distraction she caused to save his case. Hoping to return the favor, he turns to a good friend--and one of high society's leaders--to take Adelaide in hand and turn her fashionable. When danger surrounds them and Adelaide finds herself a target of the criminals in Gideon's case, the spark of love between them threatens to be quenched for good--along with their lives" --